Detection and screening of obstructive sleep apnea in primary care - Abdullah, Marwah Yakoop; Kailani, Abdulrahman Hasan; Alnasser, Ali Malik; Alqari, Hisham Hamdoon; Alharbi, Shahd Ayed; Alshahrani, Saeed Saad; Alzahrani, Shahad Idhah; Fageeh, Nariman Ayman; Alharbi, Nada Waleed; Albaqami, Abdulilah Mohammed; Alsuaylik, Abdullah Mohammed (International Journal Of Community Medicine And Public Health, 2022)
The most prevalent sleep-related breathing condition, obstructive sleep apnea (OSA), is linked to greater morbidity and poor cardiovascular outcomes. Even though sleep disorders are frequently present, primary care physicians hardly see or treat them. Better OSA symptom and intensity identification and classification to support OSA evaluation and diagnosis were the first outcomes of a task group of the American Academy of Sleep Medicine that produced quality metrics for the treatment of adult patients with the condition in 2015. The OSA screening tools (Berlin questionnaire, Epworth sleepiness scale, STOP Bang) have proven to be effective instruments for screening of sleep disorders. The present primary care practice approach for OSA screening and evaluation is disorganized and inadequate. Patients with OSA symptomatology are seen by primary care physicians, but they are not regularly screened, assessed, or referred to a sleep specialist. For the OSA screening assessments in general practice, more psychometric investigations are required. The findings from these investigations can be applied in real-world settings to improve OSA identification.